2017
DOI: 10.3844/ojbsci.2017.143.150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Metals on the Enzymatic Activity of Haplic Chernozem under Model Experimental Conditions

Abstract: The biological activity of soils is an essential parameter of their ecological status. The anthropogenic Heavy Metals (HMs) disturb the normal functioning of soil biota and, hence, the entire soil system. The aim of this work was to estimate the toxicity of loosely bound HM compounds in Haplic Chernozem using parameters of cellulose-degrading and urease activities. Contamination of Haplic Chernozem with Zn, Cd, Cu and Pb enlarged the group of mobile (loosely bound to soil) metal compounds, which includes excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In soils with a lighter granulometric composition, less organic matter, and more acidic, the ecotoxicity of most pollutants will be even higher (Kolesnikov et al, 2020 , 2021 ; Guney et al, 2020 ; Minnikova et al, 2017 ). According to the degree of inhibition of biological activity in Haplic Chernozem, the studied metals formed the following series: Cd > Pb > Zn > Cu (Gromakova et al, 2017 ). The physicochemical properties of soils and technogenic load affect their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…In soils with a lighter granulometric composition, less organic matter, and more acidic, the ecotoxicity of most pollutants will be even higher (Kolesnikov et al, 2020 , 2021 ; Guney et al, 2020 ; Minnikova et al, 2017 ). According to the degree of inhibition of biological activity in Haplic Chernozem, the studied metals formed the following series: Cd > Pb > Zn > Cu (Gromakova et al, 2017 ). The physicochemical properties of soils and technogenic load affect their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Haplic Chernozems are characterized by specific distributions of free carbonates in the form of carbonate mold along with common carbonate neoformations (beloglazka and veins) (Bezuglova and Yudina, 2006;Bezuglova and Tischenko, 2012;Gromakova et al, 2017;Minkina et al, 2008;2010). Haplic Chernozems are frequently called micellar-calcareous chernozems.…”
Section: Discussionmentioning
confidence: 99%
“…Gromakova et al [74] during their work reported that the increase of mobile potentially toxic element forms content in soil inhibited the cellulose-degrading and urease activities after 30 days of the input of metal into the soil. The inhibition of biological activity of the studied metals formed the following series: Cd > Pb > Zn > Cu.…”
Section: Effects Of Potentially Toxic Elements On Soil Enzyme Activitiesmentioning
confidence: 99%